Measuring indirect effects of unfair employer behavior on worker productivity: A field experiment - Matthias Heinz; Sabrina Jeworrek; Vanessa Mertins; Heiner Schumacher; Matthias Sutter (Max Planck Institute for Research on Collective Goods, 2017)
We present a field experiment in which we set up a call-center to study how the productivity of workers is affected if managers treat their co-workers in an unfair way. This question cannot be studied in long-lived organizations since workers may change their career expectations (and hence effort) when managers behave unfairly towards co-workers. In order to rule out such confounds and to measure productivity changes of unaffected workers in a clean way, we create an environment where employees work for two shifts. In one treatment, we lay off parts of the workforce before the second shift. Compared to two different control treatments, we find that, in the layoff treatment, the productivity of the remaining, unaffected workers drops by 12 percent. We show that this result is not driven by peer effects or altered beliefs about the job or the managers' competence, but rather related to the workers' perception of unfair behavior of employers towards co-workers. The latter interpretation is confirmed in a survey among professional HR managers. We also show that the effect of unfair behavior on the productivity of unaffected workers is close to the upper bound of the direct effects of wage cuts on the productivity of affected workers. This suggests that the price of an employer's unfair behavior goes well beyond the potential tit-for-tat of directly affected workers.
Keywords: C93; J50; J63; 330; Gift exchange; Layoffs; Labor Markets; Fairness; Field Experiment